2011
DOI: 10.4028/www.scientific.net/amr.356-360.236
|View full text |Cite
|
Sign up to set email alerts
|

Study on Chromosome Aberrations of Crosses Between 3E Disomic Addition Line and 2C Addition Line

Abstract: Thinopyrum elongatum, a wild relative of wheat, can be used as an excellent source of disease and abiotic stresses resistance and carries several useful traits, which have been transferred into wheat by interspecific hybridization. The most effective method of transferring the profitable genes of Th. elongatum into wheat is to induce chromosome recombination by the gametocidal system. In this study, cross, backcross and selfcross were performed between Chinese Spring-Th. elongatum 3E disomic addition line and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Kang et al (2011) found that introgression of chromosome 3Ns from Psathyrostachys huashanica into wheat could also provide resistance to stripe rust. Guo et al (2011) demonstrated that the T. ponticum 3E chromosome carries stripe rust resistance genes and showed excellent salt tolerance;…”
Section: Discussionmentioning
confidence: 99%
“…Kang et al (2011) found that introgression of chromosome 3Ns from Psathyrostachys huashanica into wheat could also provide resistance to stripe rust. Guo et al (2011) demonstrated that the T. ponticum 3E chromosome carries stripe rust resistance genes and showed excellent salt tolerance;…”
Section: Discussionmentioning
confidence: 99%